KESALAHAN SISWA PADA KATEGORI KEMAMPUAN AWAL MATEMATIS RENDAH DALAM PENYELESAIAN TES KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Galih Kurniadi; Jayanti Putri Purwaningrum (Universitas Sultan Ageng Tirtayasa, 2018)
One of the goals of learning mathematics is that students have the ability to solve mathematical problems. The objectives of this research are to: (1) Analyze students' errors in categories of low basic mathematical ability in completing tests of mathematical problem solving skills; and (2) to know the cause of the mistakes made by the students on the category of low basic mathematical ability. This research uses descriptive qualitative approach. The subjects of the study were 9 students of grade 5th SD N 4 Puyoh, Kabupaten Kudus selected from the category of early mathematical ability of low level students. Subjects are selected by considering the teacher's explanation in the research class about the students' ability to express opinions or the oral way of thinking. The determination of research subjects is based on the results of students 'problem solving skills tests and students' maths early test. Methods of data collection in this study are early mathematical ability test, problem solving test, and interview. Data analysis in this research is done with stages that include data reduction, data presentation, and draw conclusion and verification. The results showed that the cause of the mistakes made by students in completing the test of mathematical problem solving ability in the low student group are: (1) Students do not read the problem carefully so that there is information that is missed; and (2) Students can not mention what is known completely, do not identify what is known exactly so that it causes incorrect interpretation. Keywords: Mathematic, Problem Solving Test, Student’s Error